Pendidikan Karakter di Sekolah Dasar/Madrasah Ibtidaiyah Berbasis Pemberdayaan Pikiran Bawah Sadar - Andi Prastowo (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2018)
National Education in Indonesia is still covered with a variety of issues. One of them is the moral degradation among students. Although since 2010 has imposed an integrated character education in schools, but these conditions indicate the character education has not been done properly. This was especially the case in elementary school. Because at this level attitude formation is a major concern compared to the cognitive and psychomotor. The learning process is integrated with learning characters of various subjects in primary schools should be done not just in a state of conscious mind (conscious mind), but it is more empowered is to condition the subconscious mind when active. To that end, the character of the learning process must be carried out under conditions that do with relaxation hypnosis, mind focus and the alpha state, the subconscious communication, reps, make braided rapport with learners, the information conveyed in the imprint, the message is delivered in a condition of intense emotions, affirmation and visualization. With such a mechanism learners belief system can be programmed or reprogrammed as expected character. Through this belief system changes can be found changes in the character of learners effectively and relatively fixed.